Evaluation of anhydrosugars as a molecular proxy for paleofire activity: A case study on a Holocene sediment core from Agios Floros, Peloponnese, Greece. (March 2021) - Norström, Elin; West, Johannes; Kouli, Katerina; Katrantsiotis, Christos; Hättestrand, Martina; Smittenberg, Rienk H.
Highlights: Summed anhydrosugars (SAS) are tested as a fire-proxy in Greek sediments. Presence of SAS in modern soils indicates recent fire activity. Fossil SAS are affected by vegetation type, fire behavior and preservation conditions. Highest SAS were found during wet phases and when forest vegetation dominated. Fossil charcoal infers high fire activity 4400–2800 cal yr BP (Bronze Age) Abstract: The anhydrosugars, levoglucosan, mannosan and galactosan, are regarded as suitable molecular indicators of natural biomass combustion. Here, we evaluate summed anhydrosugars (SAS) as a paleofire indicator in a 6000 year-long fossil core from Agios Floros fen, Peloponnese, Greece, by analyzing charcoal fragments in parallel, throughout the sediment sequence. Modern surface soil samples from the same region were analysed for the presence of SAS, confirming the biomarker as an indicator of recent fire activity. The highest SAS concentrations in the fossil core were found in sections representing periods of wet conditions, both on local and regional scales and regionally widespread arboreal vegetation. Low amounts, or the absence, of SAS in the fossil core were associated with periods of dryness, regional dominance of non-arboreal vegetation and the presence of a fen rather than a lake ecosystem at the site. Micro-charcoal fragments were generally more abundant under these conditions. This suggests that SAS yield and deposition may vary with fuel availability and fire behavior, which in turn is affected by climate, local moisture and vegetation type. Forest fires result in more SAS compared to grass fires. SAS yield is also favored by low-temperature fires sustained under wet climate conditions. Preservation of SAS is likely to be compromised in the only seasonally wet fen ecosystem under the dry and warm Mediterranean climate conditions. The moist and shallow conditions in the wetland during hot summer months probably promote oxidation and biodegradation of the labile SAS molecules, compared to the more robust charcoal fragments. Thus, a multiproxy approach - using several proxies, both for fire, hydroclimate and vegetation change - is preferred when aiming to reconstruct past biomass burning from wetland ecosystems in a Mediterranean environment. The micro-charcoal record from Agios Floros reveals significant fire activity between 4400 and 2800 cal yr BP. This partly overlaps the Bronze Age period, associated with intense human environmental interaction and climate change in this area of Peloponnese, Greece.